GAMBARAN PENGETAHUAN SISWA KELAS X DAN XI MENGENAI MAKANAN INSTAN DI SMA NEGERI 3 CIMAHI (UPPM. Poltekkes Kemenkes Bandung, 2021)
This research is motivated by a wrong understanding of instant food in adolescents starting from what is instant food, types of instant food, to the impact of consuming instant food excessively. So that makes them too often consume instant food without realizing the nutritional content and harmful substances that are in instant food. This shows how important an understanding of instant food. This study aims to determine the description of class X and xi students' knowledge of instant food. This type of research is a quantitative descriptive using random sampling techniques with simple random sampling techniques. The number of samples of this study was 88 students. Analysis of the data used in univariate analysis with percentages. The results showed that of the 88 students there were the majority of respondents (47.7%) had good knowledge of 42 people, while those with sufficient knowledge were (45.5%) or 40 people, and those with less knowledge were ( 6.8%) or as many as 6 people. Recommendations to schools to make effective promotive actions. One way is to educate about healthy and nutritious food for students from an early age. That way teens will start paying attention to the good nutritional content that their bodies need. Key words: instant food, knowledge, teenagers